Body politics, alterities, and perception: A theological hesitation after the pandemic. Issue 4 (29th December 2021) - Kristensen, Johanne Stubbe Teglbjærg
Abstract: By demanding collective strategies and agreeing individuals, the pandemic has not only exposed multiple kinds of otherness around us and between us, but even within us. In this article, I propose to theologically reflect on this situation by means of a perceptive hesitation. I do this with reference to Wolfhart Pannenberg's theology, and Alia Al‐Sagi's critical phenomenology, both of whom draw on Henri Bergsson's descriptions of human temporality, and share the consideration of human independence as being integral to perceiving alterity. In the end, I identify where Al‐Sagi and Pannneberg differ, and I go with Al‐Sagi, and consider hesitation as a term for the temporal dimension and difference of faith as related to hope and the necessary condition for a loving body politics.